(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Further due to revision of existing codes the design seismic forces are increased and code provisions made stringent to avoid damage failures e.g., in the 2002 edition of Indian Seismic code IS 1893, Hyderabad has been upgraded to seismic zone II from seismic zone I of the 1984 edition. Hence most of the buildings which were safe as per the previous code have become unsafe as per provisions of the new code. Hence the need to determine the seismic safety of all the existing buildings and strengthen the weaken ones to resist the seismic forces prescribed by the new code. Hence the importance of this research works. Further most of the existing buildings were not designed to resist even the earthquake forces prescribed by the old code. There is greater need to evaluate the seismic safety of all such buildings as some of them may need demolition to avoid loss of life in future earthquakes. The remaining buildings will need retrofitting and repair.A constant study is carried out by varying the seismic areas, soil type and store number, etc., changing only one parameter at a time. A method for determine the seismic security of existing reinforced concrete structure based on the Indian seismic code is proposed. The results are validated by comparing them with methods currently in use in other countries. It is hoped that the method developed will be useful in presenting a more comprehensive seismic safety evaluation code for use by the Indian designers. The need for evaluation arises mainly due to two causes first, most of the existing RC buildings, particularly the old ones, have not been designed to resist earthquake forces due to lack of awareness Secondly, due to the revision of the existing seismic codes, Even buildings designed by previous codes for seismic forces can become unsafe because of the increase in the seismic forces proposed. In India, because of the revision of IS 1893-1984 in 2002, we are facing this situation. Our town in Hyderabad is now under seismic zone II, while it used to be in zone I. The main objective of the present work is to study the seismic vulnerability of existing RC buildings in Hyderabad city. Since the city Hyderabad was under Seismic Zone- I up to 2002 and after that it was in Zone II as per IS1893. All the buildings constructed before and after will be checked in accordance with latest seismic code of India.